TEACHING THE PHOTOELECTRIC EFFECT IN HIGH SCHOOL: AN INQUIRY-BASED APPROACH GROUNDED IN THE HISTORY AND PHILOSOPHY OF SCIENCE - Moura, Tiago Martins; Moura, Cristiane de Carvalho Ferreira Lima; Silva, Maria Goretti; Celedonio, Natália Rocha; Ferreira, Lidiane Martins Moura (Seven Editora, 2025)
The persistence of traditional practices in Physics Education, still centered on content exposition and the mechanical application of formulas, has hindered students’ conceptual understanding of Modern Physics topics in High School, including the Photoelectric Effect. Considering the guidelines of the Brazilian National Common Curricular Base and the need for approaches that promote problematization and scientific argumentation, this article aims to present an inquiry-based proposal for teaching the Photoelectric Effect articulated with elements of the History and Philosophy of Science. This is a theoretical-bibliographic and propositional study that systematizes a didactic organization structured around a contextualized problem situation involving light sensors. The proposal mobilizes prior knowledge, fosters hypothesis formulation and confrontation, and leads to the conceptual systematization of the quantum model of light, highlighting the limitations of the classical wave interpretation. The incorporation of historical episodes supports the understanding of transitions between explanatory models and of the nature of science. As a result, a didactic organization suitable for the school context is outlined, capable of promoting comprehension of radiation–matter interaction and the role of frequency in photoelectric emission. It is concluded that the inquiry-based approach, integrated with digital resources and formative assessment, is viable and pedagogically relevant for High School, contributing to more meaningful learning aligned with current curricular guidelines.